2000
DOI: 10.1097/00007890-200002150-00024
|View full text |Cite
|
Sign up to set email alerts
|

Renal Allograft Rejection With Normal Renal Function in Simultaneous Kidney/Pancreas Recipients

Abstract: These findings suggest that, in patients undergoing simultaneous kidney/pancreas transplantation, the entity of dissynchronous pancreatic allograft rejection without renal allograft rejection may not really exist. These data also make an additional fundamental point that acute rejection may occur in patients with normal and stable renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
1
12
1
2
Order By: Relevance
“…We have noted similar findings in a small number of simultaneous kidney/ pancreas (SPK) recipients who underwent renal allograft biopsy, despite having stable and normal renal function, because of a rising serum lipase level (i.e. suspected pancreatic rejection) (12). This demonstration of unsuspected tubulitis raised a concern that we have been systematically underestimating the incidence of acute rejection in our patients.…”
Section: Introductionsupporting
confidence: 71%
“…We have noted similar findings in a small number of simultaneous kidney/ pancreas (SPK) recipients who underwent renal allograft biopsy, despite having stable and normal renal function, because of a rising serum lipase level (i.e. suspected pancreatic rejection) (12). This demonstration of unsuspected tubulitis raised a concern that we have been systematically underestimating the incidence of acute rejection in our patients.…”
Section: Introductionsupporting
confidence: 71%
“…It is plausible that acute rejection is under-reported by the staff who enter these data for the OTPN and might have limited medical knowledge. For the DDS, acute rejection was defined by clinical diagnosis, regardless of whether antirejection treatment was given, and only a small percentage of patients underwent protocol biopsy (23)(24)(25). We did not require biopsy for the definition of acute rejection in the DDS, because the OPTN fields related to acute rejection that were used for this study also do not specify biopsy findings.…”
Section: Discussionmentioning
confidence: 99%
“…Klassen et al have reported a 27% incidence of isolated pancreas rejection in SPK (40), however, it is unclear how many of the patients in this study actually underwent simultaneous kidney and pancreas biopsies. Indeed, whether dissynchronous rejection even exists has been questioned by Shapiro et al who performed kidney biopsies in SPK patients with normal serum creatinine in the presence of clinically suspected pancreas rejection (elevated serum lipase) (41). All kidney biopsies had histologic evidence of rejection, and serum lipase improved in response to bolus steroid therapy.…”
Section: Discussionmentioning
confidence: 99%